Petrography and genesis of Vaajasalmi graphite targets in Rautalampi Central Finland - Nurkkala, Jaakko (My University, 2022)
Natural graphite is listed on the European Union's top 30 most critical minerals and is mainly imported outside of Europe. Graphite value and demand increase are driven by electrification since its extraordinary features in the conductance of electricity and heat. The Geological Survey of Finland has done wide studies on graphite in recent years and they believe the qualities of the bedrock and metamorphic grade in Finland are suitable for economically potential graphite deposits. This thesis study mineralogy and the genesis of Vaajasalmi area graphite targets in Rautalampi municipality in Central Finland. The two flake graphite targets were first discovered by the Geological Survey of Finland during the battery mineral exploration campaign. The petrographic study was conducted from 16 thin sections with polarization and reflected light microscopes. Genesis and quality of the graphite and metamorphic degree of the rocks were determined by scanning electron microscope (SEM), Raman spectroscopy, petrography. Further, the thesis solves Vaajasalmi graphite targets mineralogical properties, the difference between targets, genesis and formation temperature of the graphite. The graphite has remobilized and enriched via deformation-driven intensive shearing that also produces higher purity of graphite. Comparison to average Finnish Svecofennian sediments pseudosections gives an estimate of high amphibole facies conditions in the study area with temperatures ranging from 650 to 750 °C and pressure from 5 to 9.5 kbar. Impurities inside the graphite are derived from the surrounding minerals and the best quality graphite is associated with recrystallized-looking quartz clusters.
Keywords: Graphite, Rautalampi, Central- Finland, Raman, Geothermometer, Scanning Electron Microscopy, Petrography